Pubic Symphyseal Age Estimation from Three-Dimensional Reconstruction of Pelvic CT Scans (Journal of Forensic Medicine & Toxicology, 2026)
Background: Accurate age estimation remains a cornerstone of forensic identification. Among several skeletal markers, the pubic symphysis has emerged as a reliable site for adult age assessment due to its predictable morphological changes. Conventional methods like Todd’s and Suchey–Brooks phase systems have been widely used. However, these are primar ily based on direct skeletal examination, which may not always be feasible. This study aimed to evaluate the reliability of age estimation from three-dimensional (3D) reconstruction of pelvic computed tomography (CT) scans using estab lished morphological phase systems. the pubic symphysis has emerged as a reliable site, assessing its application in living individuals for forensic purposes in the Indian population. Materials and Methods: CT scans of adult pelvises were reconstructed in 3D and analyzed for morphological changes at the pubic symphysis. A comparative analysis was conducted between Todd’s 10-phase system, McKern-Stewart’s component-based method, Gilbert-McKern’s female-specific modification, and the Suchey–Brooks six-phase system. Morphological features such as dorsal plateau, ventral rampart, and symphyseal rim were evaluated across age and sex strata. Statistical tools were used to assess interobserver agreement, correlations, and accuracy. Results and Conclusion: 3D CT reconstructions provided clear visualization of morphological changes, facilitating precise phase identification. The Suchey–Brooks and McKern-Stewart systems showed significant concordance with chronological age, and the component-based approach demonstrated higher objectivity and repeatability. Age estimation was more reliable in males due to the confounding effect of childbirth-related changes in females. Three-dimensional CT reconstruction is a promising, non-invasive tool for age estimation using pubic symphyseal mor phology. Its application can enhance forensic accuracy in living individuals and skeletal remains, particularly in regions like India where population-specific standards are needed. Future studies should focus on creating localized databases for improved forensic applicability.
Keywords: Forensic age estimation; pubic symphysis; 3D CT reconstruction; Indian population; Forensic radiology